A CD1d-dependent lipid antagonist to NKT cells ameliorates atherosclerosis in ApoE−/− mice by reducing lesion necrosis and inflammation. (24th November 2015) - Li, Yi; Kanellakis, Peter; Hosseini, Hamid; Cao, Anh; Deswaerte, Virginie; Tipping, Peter; Toh, Ban-Hock; Bobik, Alex; Kyaw, Tin
Abstract: Aims: Atherosclerosis-related deaths from heart attacks and strokes remain leading causes of global mortality, despite the use of lipid-lowering statins. Thus, there is an urgent need to develop additional therapies. Methods and results: Reports that NKT cells promote atherosclerosis and an NKT cell CD1d-dependent lipid antagonist (DPPE-PEG350, 1, 2-dipalmitoyl- sn -glycero-3-phosphoethanolamine- N [methoxy(polyethyleneglycol)-350]) reduces allergen-induced inflammation led us to investigate its therapeutic potential in preventing the development and progression of experimental atherosclerosis. DPPE-PEG350 was administered to hyperlipidaemic ApoE −/− mice with/without established atherosclerosis. Atherosclerosis and immune cells were assessed in the aortic sinus lesions. Lesion expression of monocyte chemoattractant protein-1 (MCP-1) and vascular cell adhesion protein-1 (VCAM-1) responsible for inflammatory immune cell recruitment as well as mRNA expression of IFNγ and its plasma levels were investigated. Necrotic cores and lesion smooth muscle and collagen contents important in plaque stability were determined as were plasma lipid levels. DPPE-PEG350 reduced atherosclerosis development and delayed progression of established atherosclerosis without affecting plasma lipids. CD4 and CD8 T cells and B cells in atherosclerotic lesions were decreased in DPPE-PEG350 -treated mice. Lesion MCP-1 and VCAM-1 protein expression and necrotic core size were reduced without affecting lesion smooth muscle and collagen content. IFNγ and lymphocytes were unaffected by the treatment. Conclusion: The attenuation of progression of established atherosclerosis together with reduced development of atherosclerosis in hyperlipidaemic mice by the NKT antagonist, without affecting NKT cell or other lymphocyte numbers, suggests that targeting lesion inflammation via CD1d-dependent activation of NKT cells using DPPE-PEG350 has a therapeutic potential in treating atherosclerosis.